Analysis of consumption frequencies of vegetables and fruits in Korean adolescents based on Korea youth risk behavior web-based survey (2006, 2011) - Kim, Yangsuk (Nutr Res Pract, 2015)
BACKGROUND/OBJECTIVES: This study analyzed factors affecting consumption frequencies of vegetables and fruits in Korean adolescents. SUBJECTS/METHODS: Consumption frequencies of vegetables and fruits, general characteristics, meal, health, and other variables were analyzed for a total of 147,047 adolescents who participated in the KYRBWS (Korea Youth Risk Behavior Web-based Survey) conducted in 2006 and 2011 by the Korea Centers for Disease Control and Prevention. RESULTS: Consumption frequencies of vegetables and fruits more than once a day significantly decreased in 2011 compared to 2006 based on Chi-square test conducted for every factor employed in the study. Analysis of factors showed that consumption frequencies of vegetables and fruits were reduced in both study years as subjective income decreased, whereas intake frequencies increased with mother's education level and reduction of adolescent stress level. CONCLUSIONS: In general, consumption frequencies of vegetables and fruits decreased in 2011 compared to those in 2006. Thus, future research needs to improve dietary guidelines for nutrition education in order for students to recognize the importance of food consumption and necessity of increasing daily serving sizes of vegetables and fruits for their balanced consumption.